The minimum wage and hours per worker - Eric Strobl; Frank Walsh (University College Dublin, UCD School of Economics, 2010)
In a competitive model we ease the assumption that efficiency units of labour are the product of hours and workers. We show that a minimum wage may either increase or decrease hours per worker and the change will have the opposite sign to the slope of the equilibrium hours hourly wage locus. Similarly, total hours worked may rise or fall. We illustrate the results throughout with a Cobb-Douglas example.
hdl:10197/2661
Keywords: J22; J38; 330; Minimum wages; Hours; Employment